Productivity of late varieties of white cabbage (Brassica oleraceae L. subsp. capitata (L.) Alef. var. alba) depending on the sort types - О. Я. Жук; П. Б. Вороніна (Plant Varieties Studying and Protection)
Purpose. Conducting economic evaluations of late varieties of white cabbage of various sort types bred by Kyiv experimental station of the Institute of Vegetables and Melons NAAS of Ukraine (IVM). Methods. Field, laboratory, statistical. Results. Experimental studies included phenological observations of plants growth and development, biometric measurements of vegetative and edible parts of plants, determination of biochemical сomposition of heads, records of yield and storability of late varieties of white cabbage of such sort types as Amager and Langedijska winter. Varieties with the highest yield, best biochemical composition and excellent storability of cabbage heads during four and six month periods were identified. Conclusions. Among the cabbage samples of Amager sort types, late variety Vasylyna was characterized by the highest yields. Olga variety provided the significant increase in productivity. Violanta variety had the highest yield within the sort type Langedijska (Langendijker) winter. Knyagynіa variety far exceed indices of standard Langendijker detsema. Late varieties of the first sort type produced the highest yield, the second ones demonstrated better biochemical composition and excellent storability of cabbage heads during four and six month period.